THE SALVATION ARMY AND THE ANGLICAN CHURCH, 1882-1883. - Green, Roger J. (Fides et historia, 2015)
The article explores the proposed merger between the Church of England and the Christian denomination The Salvation Army in the late 1800s. Topics discussed include the challenges faced by the Anglican Church during the transition associated with the Industrial Revolution, the way Archbishop of Canterbury Archibald Campbell Tait acknowledged possible engagement of the Church with The Salvation Army, and the obstacles to this merger involving the Anglican hierarchy.